Sorption of lead (II), cobalt (II) and copper (II) ions from aqueous solutions by γ-MnO2 nanostructure. (January 2015) - Le, Ngoc Chung; Van Phuc, Dinh
Abstract Manganese dioxide γ-MnO2 was synthesized via the reduction–oxidation reaction between KMnO4 and C2H5OH at room temperature and characterized with x-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer–Emmet–Teller nitrogen adsorption (BET–N2 adsorption). The results showed that γ-MnO2 was about 10–18 nm in size and the BET surface area was about 65 m2 g−1. The feasibility of γ-MnO2 used as a low cost adsorbent for the adsorption of Pb(II), Co(II) and Cu(II) from aqueous solutions was explored. During the adsorption process, batch technique was used, and the effects of contact time and pH on adsorption efficiency under room temperature were studied. The adsorption data showed that the Freundlich, Langmuir and Redlich-Peterson isotherms are a good model for the sorption of Co(II) and Cu(II), while the Langmuir and Redlich–Peterson isotherms provide a reasonable fit to the experimental data for Pb(II). By using the Langmuir isotherm, the adsorption capacities for Pb(II), Co(II) and Cu(II) are found to be 200 mg g−1, 90.91 mg g−1 and 83.33 mg g−1, respectively. The effectiveness of γ-MnO2 in the sorption of the three metal ions from aqueous system has the order Pb(II) > Co(II) > Cu(II). Kinetic studies showed that a pseudo-second-order model was more suitable than the pseudo-first-order model. Also, the intra-particle diffusion models were used to ascertain the mechanism of the sorption process. It is concluded that γ-MnO2 can be used as an effective adsorbent for removing Pb(II), Co(II) and Cu(II) from aqueous solutions.